Transduction of Human CD34(+) Repopulating Cells with a Self-Inactivating Lentiviral Vector for SCID-X1 Produced at Clinical Scale by a Stable Cell Line - Greene, Michael R. (Mary Ann Liebert, Inc., 2012)
Self-inactivating (SIN)-lentiviral vectors have safety and efficacy features that are well suited for transduction of hematopoietic stem cells (HSCs), but generation of vector at clinical scale has been challenging. Approximately 280 liters of an X-Linked Severe Combined Immunodeficiency Disorder (SCID-X1) SIN-lentiviral vector in two productions from a stable cell line were concentrated to final titers of 4.5 and 7.2×10(8) tu/ml. These two clinical preparations and three additional development-scale preparations were evaluated in human CD34(+) hematopoietic cells in vitro using colony forming cell (CFU-C) assay and in vivo using the NOD/Lt-scid/IL2Rγ(null) (NSG) mouse xenotransplant model. A 40-hour transduction protocol using a single vector exposure conferred a mean NSG repopulating cell transduction of 0.23 vector genomes/human genome with a mean myeloid vector copy number of 3.2 vector genomes/human genome. No adverse effects on engraftment were observed from vector treatment. Direct comparison between our SIN-lentiviral vector using a 40-hour protocol and an MFGγ(c) γ-retroviral vector using a five-day protocol demonstrated equivalent NSG repopulating cell transduction efficiency. Clonality survey by linear amplification-mediated polymerase chain reaction (LAM-PCR) with Illumina sequencing revealed common clones in sorted myeloid and lymphoid populations from engrafted mice demonstrating multipotent cell transduction. These vector preparations will be used in two clinical trials for SCID-X1.